Implementasi Pengelolaan Iklan dalam Karnaval SCTV (Pada Tayangan Commercial Break Produk Bejo Jahe Merah) - Amanda, Sylvia; Arifputri, Aiza Nabilla; Wijaksono, Dimas Satrio; Melano, Fiqie Lavani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Television is the main medium for conveying marketing messages to the public. Managing advertisements during commercial breaks is very important to increase the attractiveness of the message to be conveyed to the audience. Through the SCTV Carnaval program, it has become one of the routine programs held every year with high appeal in the community. Therefore, commercial breaks are needed to support the SCTV Carnaval program. Through the work design “Implementation of Advertising Management in the SCTV Carnaval (On Commercial Break Bejo Jahe Merah Product)”. The author implements commercial break Bejo Jahe Merah based execute message style Armstrong & Kotler (2022) including a slice of life, lifestyle, mood or image, personality symbol, scientific evidence, and testimonial evidence for creating actual commercial break. Dara obtained from observations at the workplace, company documents, and literature studies. The result of this work design shows that the implementation of this theory can improve the quality of message execution in more up-to-date commercial break Bejo Jahe Merah.